TRAINING ON CONTRACEPTIVE SELECTION BASED ON FAMILY PLANNING ACCEPTORS’ CLINICAL CONDITIONS - Ema Pristi Yunita; Oktavia Rahayu Adianingsih; Sri Winarsih (Caring : Jurnal Pengabdian Masyarakat, 2022)
A population growth rate of 1.22% has become a national problem and makes Indonesia one of the most densely populated countries in the world. Meanwhile, the population growth rate in Malang city, which has been successfully decreasing, needs to be sustained. This community service aimed to help maintain this achievement by providing training on contraception in the pharmaceutical care aspect, especially in clinical pharmacy. It is because if the contraceptive preparation chosen is birth control pills, the choice of hormonal contraception needs to be adjusted to the family planning acceptor’s clinical condition and emphasizing the importance of medication adherence is required. The problem-solving method used in this community service activity was Participatory Action Research (PAR). Techniques for delivering material were done through presentation, training, and practices using visual aids. The activity was located at the meeting hall of RW 08, Bunulrejo Village, Blimbing District, Malang City and was carried out for two months with the highlight of the event in March 2022. Three types of questionnaire instruments used were personal data and data related to the history of contraceptive methods used, knowledge instrument, and activity evaluation instrument. The knowledge instrument has been declared valid and reliable through the results of the Pearson and Cronbach’s Alpha correlation tests. The results of this community service activity showed that 43.48% of the participants experienced class 1 obesity, and 9% suffered from comorbid hypertension. The pre-test and post-test results related to knowledge showed an increase of 32.46 points. Besides, the evaluation questionnaire of the three aspects of the assessment, including process, benefits, and training presenters, showed an average score of ≥ 3.50. In short, class 1 obesity and hypertension comorbidity are the conditions to consider when choosing hormonal contraceptive preparations for the community, although the prevalence was relatively small. Participant knowledge related to contraception increased after the training. From the evaluation questionnaire results, the participants considered that the series of training activities went very well.